PEMANFAATAN DATA MINING UNTUK KLASTERISASI POTENSI PRODUKSI BERAS DI KABUPATEN BLITAR DENGAN MENGGUNAKAN METODE FUZZY C-MEANS - Achmad Zakki Falani; Surya Agung Priambodo (SPIRIT, 2020)
Abstract : Rice production plays an important role in people's lives, where rice is a staple food that is useful so that the body can do various activities because it has an energy source. As an area included as a national rice barn, Blitar Regency has a target to increase rice production every year. Increasing the amount of rice production in Blitar must be increased to keep up with the growing population. In order to maintain and meet the needs of rice, the Blitar District government needs a method to classify rice production potential in Blitar District. The aim is to find out which areas in Blitar Regency have suboptimal rice production results. Thus the clustering technique that can be applied is the method with the Fuzzy C-Means Clustering algorithm. Using the Fuzzy C-Means method is expected to make it easier for the Blitar Regency government to classify agricultural products in Blitar Regency to find out which areas have high, medium and low rice production potential. The results of testing the Partition Coefficient validation value were 0.7695, thus the cluster quality was optimal. Keywords : Data Mining, Clustering, Fuzzy C-Means, Rice, Production, Partition Coefficient